2012
DOI: 10.1016/j.jviscsurg.2011.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Lacaine-Huguier predictive score for choledocholithiasis: Prospective study of 380 patients

Abstract: This study confirmed the validity of the Lacaine-Huguier score. When the score is less than 3.5, the surgeon can refrain from performing IOC with a risk of asymptomatic residual CBDS ranging from 0.6% to 4.5%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 21 publications
(23 reference statements)
1
10
0
2
Order By: Relevance
“…Холедохолитиаз, т.е. наличие камней в общем желчном протоке, наблюдается в 10-20% случаев у пациентов с желчнокаменной болезнью, с более низкой частотой при ОКХ, находящейся в диапазоне от 5 до 15% [119][120][121][122]. Обследование с целью выявления холедохолитиаза требует времени и может отсрочить хирургическое вмешательство.…”
Section: желчный камень в общем желчном протоке: подозрение и диагносunclassified
See 1 more Smart Citation
“…Холедохолитиаз, т.е. наличие камней в общем желчном протоке, наблюдается в 10-20% случаев у пациентов с желчнокаменной болезнью, с более низкой частотой при ОКХ, находящейся в диапазоне от 5 до 15% [119][120][121][122]. Обследование с целью выявления холедохолитиаза требует времени и может отсрочить хирургическое вмешательство.…”
Section: желчный камень в общем желчном протоке: подозрение и диагносunclassified
“…Choledocholithiasis, i.e. the presence of common bile duct stones (CBDS), is reported ro occur in10% to 20% in case series of cholelithiasis, with lower incidence during ACC ranging from 5% to 15% of the patients [120][121][122][123]. Investigation for CBDS require time and can delay the surgical intervention.…”
Section: Associated Common Bile Duct Stone: Suspicion and Diagnosis Amentioning
confidence: 99%
“…Pradėjus plačiai taikyti ERCP, atsirado poreikis nustatyti atvejus, kada procedūra reikalinga. Yra nemažai modelių ar vertinimo sistemų TLA tikimybei apskaičiuoti, dauguma jų remiasi klinikiniais, biocheminiais ir ultragarso duomenimis [28][29][30][31][32][33][34][35][36][37]. TLA vertinimo sistemų reziumė pateikta 1 lentelėje.…”
Section: Tla Rizikos Vertinimo Sistemosunclassified
“…Surgical cholecystectomy (laparoscopic or open) is commonly used for treating patients with symptomatic gallstones. Prediction of asymptomatic concurrent common bile duct stones (CBDS), which occur in 10-15% of patients, is an important factor in terms of reduction of operative risks and health care costs [3]. In establishing a firm diagnosis, the standard preoperative diagnostic procedures used to diagnose patients with gallstones (liver function tests [LFTs] and abdominal ultrasound [US]) or risk factors for CBDS (abnormal LFTs, jaundice, bile duct dilation [BDD]) are often found not to be accurate enough [4].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, non-invasive methods for diagnosis of CBDS such as prognostic model have been shown to be a desirable goal [7,8]. Previous studies have suggested various predictive models relying on logistic regression [9,10], regression trees [11], multivariate regression [3,[12][13][14], discriminant functions [15] and artificial neural networks (ANNs) for predicting CBDS [16].…”
Section: Introductionmentioning
confidence: 99%